BEST PRACTICE PROGRAMME IN THE STANDARDISATION OF TRADITIONAL MEDICINES: EVALUATION OF AN IMMUNE BOOSTER FORMULATED BY TRADITIONAL HEALERS OF THE VAAL TRIANGLE, SOUTH AFRICA - Pinkoane, M.G.; Ngcobo, M.; Gqaleni, N. (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: Regulation and standardization of African traditional medicines (ATM) prescribed by traditional healers in SouthAfrica is still far from being implemented. This is despite the fact that more people are using ATM products than ever. In an effort todemonstrate that collaboration with traditional health practitioners (THPs) can yield standardized TM products, this study aimed toevaluate the immunomodulatory effects of an herbal immune booster formulated by traditional healers from the Vaal Region, SouthAfrica.Materials and Methods: Using normal and lipopolysaccharide (LPS) stimulated human peripheral blood mononuclear cells(PBMCs) models, doses of the immune booster ranging from 1000 to 10 μg/mL were evaluated for their cytotoxicity, inflammatorycytokines and chemokines secretion, nitric oxide (NO) secretion, malondialdehyde (MDA) assay, and 1,1-diphenyl-2-picrylhydrazyl(DPPH) assay.Results: The immune booster induced a dose dependent cytotoxic effect on both normal and LPS stimulated PBMCs with higherdoses showing cytotoxicity while lower dose from 100μg/mL did not show any cytotoxicity. When re-dissolved in aqueous PBSimmune booster doses up to 100 μg/mL showed better DPPH radical inhibition (41%) than ascorbic acid at 40μg/mL (33%). Theimmune booster also decreased lipid peroxides significantly (p< 0.05) and this was comparable to ascorbic acid. There was also asignificant (p< 0.05) increase in nitrite (NO) after treatment of LPS stimulated PBMCs with immune booster doses when comparedto untreated samples. The immune booster stimulated inflammatory cytokines secretion in normal PBMCs (IL 1α, IL 1β, IL 6, IL 10and TNFα while showing a decrease in IFNγ at the higher dose) while in LPS stimulated PBMCs some cytokines were decreased (IL1α, IL 17α and at lower doses IL 10 and TNFα) and others were increased (IFNγ, TNFα and GM-CSF) depending on the dose used.In both normal and LPS stimulated PBMCs the immune booster significantly (p< 0.05) increased (MIP 1α) while causing significant(p< 0.05) decreases in IP 10 (high dose), I-TAC and MIG secretion.Conclusions: This immune booster showed potential immunostimulatory effects by increasing nitric oxide, inflammatory cytokinesand chemokines secretion in both normal and LPS stimulated PBMCs. This TM also showed promising antioxidant potential in theMDA and DPPH assays. Further in vitro and animal studies are warranted.